Do rights to resistance discipline the elites? An experiment on the threat of overthrow - Konstantin Chatziathanasiou; Svenja Hippel; Michael Kurschilgen (Max Planck Institute for Research on Collective Goods, 2020)
The threat of overthrow stabilizes a constitution because it disciplines the elites. This is the main rationale behind rights to resistance. In this paper, we test this conjecture experimentally. We model a society in which players can produce wealth by solving a coordination problem. Coordination is facilitated through a pre-game status-ranking. Compliance with the status hierarchy yields an efficient yet inequitable payoff distribution, in which a player's wealth is determined by her pre-game status. Between treatments, we vary (a) whether overthrows - which reset the status-ranking via collective disobedience - are possible or not, and (b) whether voluntary redistributive transfers - which high-status players can use to appease the low-status players - are available or not. In contrast to established thinking we find that, on average, the threat of overthrow does not have a stabilizing effect as high-status players fail to provide sufficient redistribution to prevent overthrows. However, if an overthrow brings generous players into high-status positions, groups stabilize and prosper. This suggests an alternative rationale for rights to resistance.
Keywords: C72; C92; D74; H23; P48; 330; rights to resistance; civil resistance; constitutional stability; redistribution; coordination; battle of the sexes; experiment